Ethical leadership and inclusive governance in India: Role of political parties - Sangita, S.N. (2013)
Ethical political leaders in public life are central to promote efficient, equitable, transparent, responsive and accountable governance. An analysis has been made here on the nature and pattern of ethical political leadership in India over the years with a view to understand its relation with the society and political parties. The important issues raised are: how ethical leaders' effect inclusive governance? What are the factors responsible for the decline of ethical leadership? To what extent, these factors can be attributed to society, which is responsible for socialisation and inculcation of values and selection of leaders? Or to what extent these factors can be attributed to political parties (ideologies, socialisation and internal democracy), electoral laws and ethical institutions. - Reproduced.
Keywords: Public administration - India; Leadership - India; Leadership